Islamic Capitalism? The Turkish Hizmet Business Community Network in a Global Economy - Dreher, Sabine (Journal of business ethics, 2015)
The paper develops a critique of the prevailing essentialist and homogenizing approach to business ethics that dominates the field with regard to Islam and proposes a constructivist perspective to the study of religion. It demonstrates the possibilities of this approach with the study of hizmet, a community business network from Turkey that has established itself in over 130 countries over the last 20 years. The implications for business ethics from the study of this movement is that the notion of corporate social responsibility needs to be adjusted in order to accommodate the hizmet approach but that there are limits to this adjustment due to gender and labor rights considerations. The paper sees itself as a contribution to an alternative approach for Islamic business ethics very much in need of further development and encourages further research along these lines.